2015
DOI: 10.3844/ajavsp.2015.14.22
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Rumen Papillae During the Periparturient Transition in Holstein Dairy Cows are Accompanied by Changes in Abundance of Proteins Involved in Intracellular pH Regulation, But not SCFA Transport

Abstract: Abstract:The objective of this study was to examine changes in SCFA transport capacity in the rumen epithelium during the parturition transition period. Twelve pregnant, cannulated primiparous and multiparous cows were fed a standard Total Mixed Ration (TMR) for the duration of the dry period; after calving, all cows were switched to an early lactation TMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Decreased NHE3 abundance could be a factor of age or an acidifying response of the epithelium during the weaning transition; it is also possible that other transporters that were not measured, such as NHE1, were involved. A similar response is seen in decreased expression of carbonic anhydrase 2 in mature cows going through the lactation transition, suggesting that pH i acidification may be taking place as part of an adaptive response to a highly fermentable diet (Laarman et al, 2015). It is important to note that the pH i regulatory transporters measured here are only a few of the transporters relevant to pH i homeostasis; thus, this study represents only a snapshot of the total pH i regulatory response.…”
Section: Effects Of Weaning On Regulators Of Volatile Fatty Acid Absorption and Intracellular Ph In Holstein Calvessupporting
confidence: 51%
See 1 more Smart Citation
“…Decreased NHE3 abundance could be a factor of age or an acidifying response of the epithelium during the weaning transition; it is also possible that other transporters that were not measured, such as NHE1, were involved. A similar response is seen in decreased expression of carbonic anhydrase 2 in mature cows going through the lactation transition, suggesting that pH i acidification may be taking place as part of an adaptive response to a highly fermentable diet (Laarman et al, 2015). It is important to note that the pH i regulatory transporters measured here are only a few of the transporters relevant to pH i homeostasis; thus, this study represents only a snapshot of the total pH i regulatory response.…”
Section: Effects Of Weaning On Regulators Of Volatile Fatty Acid Absorption and Intracellular Ph In Holstein Calvessupporting
confidence: 51%
“…This may be due to additional bicarbonate influx via NBC1 in an attempt to regulate pH i (Müller et al, 2000). Increasing the diet fermentability, which occurs around weaning, decreases pH i homeostatic capacity (Laarman et al, 2015) and increases passive VFA absorption (Schurmann et al, 2014) in mature ruminants.…”
Section: Effects Of Weaning On Regulators Of Volatile Fatty Acid Absorption and Intracellular Ph In Holstein Calvesmentioning
confidence: 99%
“…The amount of SCFA absorbed by the mucosa can be affected by increasing the dimensions of the RP. In cattle, morphological changes in RP were observed as early as the first week after switching from high‐fiber diet to diet rich in crushed grains (Laarman et al, 2015). During the period of adaptation to the new diet, passive diffusion is responsible for the absorption of most of the SCFA.…”
Section: Discussionmentioning
confidence: 99%
“…However, these observations do not seem to offer an explanation for the contrast between changes in papillae surface area and k a VFA. Conversely, Laarman et al (2015) reported recently that transition into lactation did not coincide with changes in expression of VFA transporter proteins. Monocarboxylate transporter MCT1 was not affected by a treatment or lactation stage effect but an interaction was observed showing a temporary increase at 16 d pp compared with 3 and 44 d pp for the rapid concentrate treatment.…”
Section: Functional Adaptation Of the Rumen: Fractional Absorption Ramentioning
confidence: 81%